KARAKTERISTIK DAN PERSEPSI PETANI TERHADAP INOVASI TEKNIK SOIL BIOENGINEERING UNTUK MITIGASI LONGSOR DI KABUPATEN BANJARNEGARA JAWA TENGAH (Characteristics and farmers’perception to Soil Bioengineering technique for mitigation of landslide at Banjarnegara Regency, Central Java ) - Baharinawati Wilhan Hastanti; Pranatasari Dyah Susanti (Center for Implementation of Standards for Environmental and Forestry Instruments Solo, 2019)
ABSTRACTSoil Bioengineering technique is a soil and water conservation technology innovation for landslide mitigation. The success of technological innovation is influenced by the perception and characteristic of the user community. This study aimed to determine the characteristics of farmers as potential users and their perceptions that were measured based on an assessment of characteristics of technology innovation. This study used a qualitative approach combined with the support of qualitative data quantification. Data collected consist of primary data and secondary data. Primary data include the characteristics of respondents and their perceptions of Soil Bioengineering innovation in the form of assessment variables consisting of certain indicators which are then measured using a Likert scale. The characteristics of farmers prospective users of Soil Bioengineering techniques are: 1) productive age, 2) lack of education (junior high school), 3) narrow land ownership (0.1 to 0.3 hectares), 4) the commodity planted is salak, 5) experience as farming (16 - 20 years) and, 6) medium/ middle income levels (3- 4.9 million rupiah per month). Farmer's perceptions are generally positive to Soil Bioengineering. Positive perception techniques if it was measured based on: 1) relative advantage, 2) compatibility, 3) simplicity, 4) trialability and 5) observability.Keywords: perception; community; innovation; technique; soil bioengineering; mitigation;landslide ABSTRAKTeknik Soil Bioengineering merupakan inovasi teknologi konservasi tanah dan air untuk mitigasi longsor. Keberhasilan inovasi teknologi ini dipengaruhi oleh persepsi dan karakteristik masyarakat pengguna. Penelitian ini bertujuan untuk mengetahui karakteristik petani sebagai calon pengguna dan persepsinya yang diukur berdasarkan penilaian terhadap karakteristik inovasi teknik Soil bioengineering. Penelitian ini menggunakan pendekatan kualitatif yang dipadukan dukungan kuantifikasi data kualitatif. Data yang dikumpulkan berupa data primer dan data sekunder. Data primer meliputi karakteristik responden dan persepsinya terhadap inovasi Soil Bioengineering yang berupa variabel-variabel penilaian yang terdiri dari indikator-indikator tertentu yang kemudian diukur dengan menggunakan skala Likert. Karakteristik petani calon pengguna Teknik Soil Bioengineering adalah: 1) berusia produktif, 2) berpendidikan rendah (SMP), 3) luas kepemilikan lahan yang sempit (0,1 sampai 0,29 hektar), 4) komoditi yang ditanam adalah salak, 5) Berpengalaman sebagai bertani (16 – 20 tahun) dan, 6) tingkat pendapatan yang sedang/ menengah (3- 4,9 juta rupiah per bulan). Persepsi petani umumnya positif terhadap teknik Soil Bioengineering. Mempunyai persepsi positif bila diukur berdasarkan: 1) keuntungan relatif, 2) kesesuaian, 3) kesederhanaan, 4) ketercobaan/ dapat dicoba dan 5) keteramatan/ dapat diamati.Kata kunci: persepsi; masyarakat; inovasi; teknik; soil bioengineering; mitigasi; longsor